Exploring Carbon Disclosure Research for Future Research Agenda: A Bibliometric Analysis - Yadiati, Winwin; Meiryani, Meiryani; Lindawati, A. S. L.; Wahyuningtias, Dianka; Daud, Zaidi Mat; Lusianah, Lusianah (International Journal of Energy Economics and Policy, 2024)
Globally, people are becoming more interested in the issue of climate change, particularly as it relates to carbon emissions. Stakeholders are putting pressure on firms to disclose more details about their ecological footprints and greenhouse gas emissions. Finding authors, publications, journals, and discoveries in the literature on emission carbon disclosure is the aim of this endeavor. To do this, we employ a review methodology that makes use of the bibliometric study technique to pinpoint a few pertinent elements found in the literature. Utilizing tools such as VOSviewer and biblioshiny from RStudio, we examine output by year, authors, articles, and publications that have received more citations. We outline the key developments in the field of carbon disclosure together with the most widely applied ideas. Furthermore, we formulate the notion of carbon disclosure as suggested by Borghei (2021), concentrating on six domains and primary patterns within the field: Provide answers to the following questions: strategic climate, carbon disclosure determinants, carbon disclosure guarantee, quality of carbon disclosure, and carbon disclosure consequences. The incorporation of sustainability dimensions into the reporting system has replaced the evaluation techniques of the disclosures as the research issue. It is discovered that a number of factors influence the corporation’s choice to release its environmental accounting information. Based on its findings and analysis of current research trends and themes, this study offers suggestions for further investigation.